Development of a project of a set of measures for the organization and monitoring of scientific and personnel support as the development of import-substituting industries - S. V. Novikov; G. V. Tikhonov (Путеводитель предпринимателя, 2020)
The article deals with the issues related to the development of the draft set of measures for the organization of scientific, technical and personnel support of projects for the creation and development of import-substituting industries in the medium and long term. A significant place in the work is given to the recommendations on the formation of scientific and technological priorities of research and development related to the provision of import substitution in selected industries and sectors of industry.